2014
DOI: 10.1007/s13312-014-0491-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and outcome of clinical BCG disease in infants

Abstract: Objective: To describe the clinical profile, immunological status and outcome of BCG disease in infants. Methods: All infants with a diagnosis of BCG disease in a period of 17 months were followed up. Results: Among 25 infants with BCG disease; 19 had local/ regional involvement and 6 had suspected or confirmed distant/disseminated disease, Mean (range) age of presentation was 3.6 (1.5-9) months. Two of 6 infants with disseminated disease required second-line anti-tubercular treatment. One infant with confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
0
8
0
2
Order By: Relevance
“…Although Inborn Errors of Immunity (IEI) as a group have been traditionally described to cause susceptibility to a wide range of micro-organisms, MSMD causes predisposition to infection by selective intracellular organisms. BCG related complications may be the presenting manifestation in MSMD in 4-80% of the patients (15). The practice of vaccinating all babies soon after birth might be the reason for an early presentation seen in our cohort; in addition to other well-known social factors like high population density, high incidence of M. tb in the country, poor nutrition, and unhygienic conditions.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Although Inborn Errors of Immunity (IEI) as a group have been traditionally described to cause susceptibility to a wide range of micro-organisms, MSMD causes predisposition to infection by selective intracellular organisms. BCG related complications may be the presenting manifestation in MSMD in 4-80% of the patients (15). The practice of vaccinating all babies soon after birth might be the reason for an early presentation seen in our cohort; in addition to other well-known social factors like high population density, high incidence of M. tb in the country, poor nutrition, and unhygienic conditions.…”
Section: Discussionmentioning
confidence: 70%
“…There is a paucity of literature on MSMD from India with only a few published case reports (12)(13)(14)(15). In this study, we report clinical, immunological, and molecular characteristics of a retrospective cohort of 55 MSMD patients from 10 centers across India.…”
Section: Introductionmentioning
confidence: 97%
“…The positive predictive value of BCG‐itis in predicting an underlying IEI is 32.6% as depicted in Table . The lower predictive value of BCG‐itis can be explained by the fact that non‐suppurative lymphadenitis may be considered part of the normal course of BCG vaccination and resolves spontaneously over a few weeks to months 35 …”
Section: Discussionmentioning
confidence: 99%
“…A study from India reported that 75% of infants with BCG-related disease have regional or localized involvement, whereas only 25% had disseminated disease. 14 Among patients with disseminated disease, only one patient had IFNγ-R1 gene mutation. 14 The use of two different strains for vaccination in the same population, one with and the other without the mpb64 gene, further complicates the problem of identification.…”
Section: Discussionmentioning
confidence: 99%